Efecto de diferentes tipos de abonos sobre hongos edáficos en el agroecosistema de Bothriochloa pertusa, (L) A. Camus, en Sabanas sucreñas, Colombia (2020)
he objective of this work was to evaluate the effect of organic and chemical fertilization applied during the dry and rainy season on the population density of rhizosphere fungi in the agrocosystem of Bothriochloa pertusa in the sabanas of Sucre, Colombia. For the in-situ evaluation of fertilizers a plot of 2280 m2 was selected, defining an area of 1848 m2; using a completely randomized block with measures repeated for the climatic seasons (dry, rainy). The treatments were: TEST control, ABM mineral fertilizer-urea, COMP chicken manure compost, COMB cattle manure compost and LOMB vermicompost. In the chemical fertilizer was applied 218 kg / ha of urea (46%), and in the organic, 1.5 tonnes / ha of organic fertilizer. To determine the effect of fertilizers on the population density of fungi (CFU/g) present in the treatments were used simple correspondence analysis, and to relate the abundance of fungi with chemical parameters of soil treatment was performed Canonical Correspondence Analysis. The data were analyzed in the statistical program R. Vermicompost treatment during the study showed the greatest diversity of fungal group: Dematiaceae, Moniliaceae, Asprgillus sp, Penicillium sp and Humicola sp. In the dry season, all soils with the respective fertilizers had higher densities, showing the highest value Vermicompost with Dematiaceae. It is concluded that the soil with the treatment vermicompost presented the best microbiological conditions in two climatic periods, these microorganisms being more abundant in the dry season.